Electromechanical Transmission of Skid Steer Loader - Khomichev Alexey (EDP Sciences, 2021)
The article analyzes the power train components of skid steer loaders. The choice of the scheme and the design of the transmission units of the loader with a traction electric drive is substantiated. The results of calculating the traction characteristic of the straight-line movement of the loader taking into account different values of the coefficient of resistance to movement are presented.